The role of notch signaling pathway in cancer: mechanistic insights, therapeutic potential, and clinical progress - Zhang, Haokun; Hang, Wang; Jing, ZhaoHui; Liu, Bingyan; Wang, Xiaoxiao; Li, Yilin; Luo, Huomin; Lv, Huilin; Tao, Xingyue; Timashev, Peter; Li, Yuzhen; Li, Peifeng (Frontiers in Immunology, 2025)
This article presents a comprehensive literature review on the role of the Notch signaling pathway in cancer and its molecular mechanisms. The Notch signaling pathway plays an important role in various types of cancer by regulating key biological processes such as epithelial-endothelial transition, angiogenesis, apoptosis and metabolic reprogramming. This article reviews the relevant mechanisms of the Notch signaling pathway in colorectal cancer, ovarian cancer, oral squamous cell carcinoma, gastric cancer and chronic lymphocytic leukemia, highlighting its dual roles in promoting tumor growth, inhibiting tumor progression and potential therapeutic applications in oncology. Meanwhile, the key roles of the Notch signaling pathway in regulating tumor drug resistance and shaping the tumor microenvironment are discussed, highlighting its importance in clinical applications. Through this review, some ideas and hints for future research directions can be provided to the readers of Notch pathway related research.